2021
DOI: 10.3389/fnins.2021.699176
|View full text |Cite
|
Sign up to set email alerts
|

Making the Invisible Visible: Advanced Neuroimaging Techniques in Focal Epilepsy

Abstract: It has been a clinically important, long-standing challenge to accurately localize epileptogenic focus in drug-resistant focal epilepsy because more intensive intervention to the detected focus, including resection neurosurgery, can provide significant seizure reduction. In addition to neurophysiological examinations, neuroimaging plays a crucial role in the detection of focus by providing morphological and neuroanatomical information. On the other hand, epileptogenic lesions in the brain may sometimes show on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 95 publications
(120 reference statements)
0
7
0
2
Order By: Relevance
“…4.1.2 | Diffusion-Weighted MRI Diffusion-weighted MRI helps to lateralize and to localize the EZ. 22 A diffusion-weighted MRI study in extra-temporal lobe epilepsy (ETLE) demonstrated the usefulness of diffusion tensor imaging (DTI) to localize the EZ when coupled with positron emission tomography (PET) using 18 Fluor-labeled fluorodeoxyglucose ( 18 F-FDG-PET). Nevertheless, no significant results were detected in the single case of insular epilepsy.…”
Section: Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…4.1.2 | Diffusion-Weighted MRI Diffusion-weighted MRI helps to lateralize and to localize the EZ. 22 A diffusion-weighted MRI study in extra-temporal lobe epilepsy (ETLE) demonstrated the usefulness of diffusion tensor imaging (DTI) to localize the EZ when coupled with positron emission tomography (PET) using 18 Fluor-labeled fluorodeoxyglucose ( 18 F-FDG-PET). Nevertheless, no significant results were detected in the single case of insular epilepsy.…”
Section: Etiologymentioning
confidence: 99%
“…24 4.1.4 | Perfusion MRI Arterial spin labeling (ASL) can assess brain perfusion and detect blood flow changes around the EZ during the interictal period. 22 Nevertheless, there is no detailed description of ASL application in insular epilepsy. 4.1.5 | Functional MRI Functional MRI combined with electroencephalography (EEG-fMRI) could help to characterize the changes in blood oxygen level-dependent (BOLD) signal associated with interictal epileptiform discharges (IEDs) recorded during fMRI data acquisition.…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 99%
“…The previous so-called 'cryptogenic epilepsy' cases by 1.5T MRI system turned out to be lesional cases after being rescanned by 3T MRI system with multichannel phased-array coils (Figure 2). Some centres are now using a 7T MRI system to confirm the suspicion in 3T MRI and locate any subtle lesions [16][17][18]. Apart from the increased signal-to-noise ratio, postprocessing of MRI images by the application of voxel-based morphometric analysis using morphometric analysis program (MAP) is another emerging direction to detect those subtle epileptogenic foci [13,19,20].…”
Section: Neuro-imagingmentioning
confidence: 99%
“…Для визуализации использовали систему Streptavidin-Peroxidase Polymer, Ultrasensitive и хромоген DAB (Sigma-Aldrich, США), срезы докрашивали гематоксилином Джилла, заключали в синтетическую заливочную среду Bio Mount HM (Bio-Optica, Италия). Оценка результата реакции проводилась путем подсчета денситометрической плотности окрашенных клеток относительно фоновых областей в 10 полях зрения в программе PhotoM 1.21 2 .…”
Section: исследование гистологических образцов головного мозгаunclassified
“…Доля пациентов с эпилепсией составляет 1% от общего числа всех заболеваний [1]. Несмотря на успехи фармакологии, у более чем 30% пациентов заболевание прогрессирует до формирования лекарственно-устойчивой эпилепсии и нуждается в хирургическом лечении [2]. Развитие резистентности к противоэпилептическим средствам может быть связано с нарушениями проницаемости гематоэнцефалического барьера (ГЭБ).…”
unclassified